Demodex folliculorum Infestation in Meibomian Gland Dysfunction Related Dry Eye Patients - Hao, Yiran; Zhang, Xiaoyu; Bao, Jiayu; Tian, Lei; Jie, Ying (Frontiers in Medicine, 2022)
Objective: To report the influence of Demodex folliculorum (D. folliculorum) infestation in patients with meibomian gland dysfunction (MGD) related dry eye and the associations of the infestation with MGD related dry eye. Methods: Eyelashes (3 from the upper eyelid and 3 from the lower eyelid) from 119 eyes of 119 patients diagnosed with MGD related dry eye were examined under a light microscope. There were 68 eyes of 68 patients with MGD related dry eye and D. folliculorum infestation (Demodex positive group) and 51 eyes of 51 patients without infestation (Demodex negative group). All patients completed an Ocular Surface Disease Index (OSDI) questionnaire and underwent tests for dry eye and MGD. The tests included fluorescein tear breakup time (TBUT), corneal fluorescein staining, SchirmerⅠtest (SIT), lid margin abnormalities, meibum expression assessment, and meibomian gland dropout. Results: The scores for OSDI, corneal fluorescein staining, lid margin abnormalities, meibum expression, and meibomian gland dropout were significantly higher (all P<0.05), while TBUT was significantly shorter in the Demodex positive group compared to the Demodex negative group (P=0.020). The SIT values did not significantly differ between groups. Chalazion was significantly more prevalent in the Demodex positive group. The number of D. folliculorum was positively correlated with all three MGD parameters (P≤0.035), OSDI; corneal fluorescein scores, and it was inversely correlated with BUT. The correlation for SIT was R2 = 0.075 (P = 0.064). Conclusion: D. folliculorum infestation is possibly one of the key contributors in the pathogenesis of MGD related dry eye, and a higher prevalence of chalazion was found in D. folliculorum infected patients. The possible causal role of D. folliculorum infestation needs to be further studied.